Factors Associated with Blood Pressure Control Among Hypertensive Patients Enrolled in the National Health Insurance Program at an Affiliated Clinic - Setiawan, Sona; Pujiyanto (Greenation Publisher & Yayasan Global Research National, 2025)
Hypertension is a major risk factor for cardiovascular disease and remains a persistent challenge in health systems, including in Indonesia. The Chronic Disease Management Program (Prolanis) under the National Health Insurance scheme (Jaminan Kesehatan Nasional, JKN) aims to improve the control of chronic diseases. However, the achievement of blood pressure control indicators at a clinic affiliated with JKN remains suboptimal. This study aimed to identify factors associated with blood pressure control among hypertensive patients enrolled in the JKN program. A cross-sectional quantitative design was applied to 120 hypertensive patients selected through quota sampling. Data were collected using standardized questionnaires (IPAQ, PSS-10, MMAS-8, and MSPSS) and analyzed using Chi-Square tests and multiple logistic regression. Results showed that 50.8% of respondents had controlled blood pressure. Among all variables examined, only physical activity was statistically associated with blood pressure control (p = 0.020; OR = 9.5; 95% CI: 1.74–51.53; p = 0.009). These findings highlight the importance of strengthening promotive and preventive approaches—particularly through structured physical activity and health education—as part of the Prolanis service to support sustainable blood pressure control.